SOCIAL DETERMINANT OF COVID-19 RISKS AMONG CHILDREN IN JAKARTA, INDONESIA - Purwati, Nyimas Heny; Awaliah, Awaliah; Imroatun, Tri (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Pandemics have historically disproportionately impacted the poor and disadvantaged. Poverty, the external environment, and race or ethnicity can all significantly impact COVID-19 consequences. Those barriers, called social determinants of health (SDOH), are significant for many people's health. This study aimed to investigate the social determinants of COVID-19 risk among children in Jakarta, Indonesia. We recruited parents whose children were between 6 and 12 and were admitted to a general public hospital in Jakarta, Indonesia. Logistic regression was used to examine the relationship between socioeconomic status and COVID-19 risk. This analysis includes 200 parents of children aged 6 to 12 years old (60%) retrospectively recruited. About half of the parents had undertaken primary education level. No significant correlation was found between parent education level, occupation, and monthly income with COVID-19 risk among children. The number of house occupants more than two was positively associated with a higher risk of COVID-19 in children. In conclusion, poor housing conditions increase the probability of COVID-19 infection in Indonesian children. This implies that parental reinforcement of anti-household transmission strategies is necessary.